High Performance Graphene–C60–Bismuth Telluride–C60–Graphene Nanometer Thin Film Phototransistor with Adjustable Positive and Negative Responses. Issue 10 (7th February 2023) - Pan, Rui; Cai, Yuanlingyun; Zhang, Feifei; Wang, Si; Chen, Lianwei; Feng, Xingdong; Ha, Yingli; Zhang, Renyan; Pu, Mingbo; Li, Xiong; Ma, Xiaoliang; Luo, Xiangang
Abstract: Graphene is a promising candidate for the next‐generation infrared array image sensors at room temperature due to its high mobility, tunable energy band, wide band absorption, and compatibility with complementary metal oxide semiconductor process. However, it is difficult to simultaneously obtain ultrafast response time and ultrahigh responsivity, which limits the further improvement of graphene photoconductive devices. Here, a novel graphene/C60 /bismuth telluride/C60 /graphene vertical heterojunction phototransistor is proposed. The response spectral range covers 400–1800 nm; the responsivity peak is 10 6 A W −1 ; and the peak detection rate and peak response speed reach 10 14 Jones and 250 µs, respectively. In addition, the regulation of positive and negative photocurrents at a gate voltage is characterized and the ionization process in impurities of the designed phototransistor at a low temperature is analyzed. Tunable bidirectional response provides a new degree of freedom for phototransistors' signal resolution. The analysis of the dynamic change process of impurity energy level is conducted to improve the device's performance. From the perspective of manufacturing process, the ultrathin phototransistor (20–30 nm) is compatible with functional metasurface to realize wavelength or polarization selection, making it possible to achieve large‐scale production of integrated spectrometer or polarization imaging sensor by nanoimprinting process. Abstract : Here, a novel graphene/C60 /Bi2 Te3 /C60 /graphene vertical heterojunction phototransistor is proposed. The transport process for photogenerated charge and local field mechanism are discussed in detail by analyzing the photoelectric performance of the device at low temperatures and different gate voltages. The device not only shows excellent photoelectric detection performance, but also exhibits substantive possibility to achieve large‐scale integrated array imaging sensors.